(untitled) - Lewis, Colin (London, Great Britain, 2005)
With plants' increasing availability at supermarkets and garden centers, the ancient art of bonsai is now accessible to anyone. This care manual explores bonsai history and details all of the techniques necessary to keep a bonsai alive and thriving. This complete guide includes the history and creation of bonsai along with step-by-step illustrations and 150 color photographs, giving readers the confidence to buy, feed, and trim these miniature trees into impressive displays in their home or garden.
Keywords: Plants, ornamental,Bonsai